Formation of Single‐Holed Cobalt/N‐Doped Carbon Hollow Particles with Enhanced Electrocatalytic Activity toward Oxygen Reduction Reaction in Alkaline Media. Issue 10 (6th July 2017) - Guan, Bu Yuan; Yu, Le; Lou, Xiong Wen (David)
Abstract: Design and construction of metal‐organic framework (MOF) composite precursors have recently been considered as a promising strategy for the preparation of different structured metal/carbon‐based functional materials. Here, an MOF composite‐assisted strategy to synthesize single‐holed cobalt/N‐doped carbon hollow particles is reported. The yolk–shell polystyrene@zeolitic imidazolate framework‐67 (PS@ZIF‐67) composite precursors are first synthesized, followed by a controlled pyrolysis to obtain cobalt/N‐doped carbon hollow particles with a large single hole on each shell. Moreover, the MOF‐coating approach reported in this work can be extended to prepare various core‐shell ZIF‐67 composites with different structures and compositions. Benefiting from the structural and compositional advantages, the as‐derived single‐holed cobalt/N‐doped carbon hollow particles manifest superior electrocatalytic oxygen reduction performance with high activity and excellent durability. Abstract : Unique cobalt/N‐doped carbon hollow particles with a single large through‐hole on the shell are synthesized using designed polystyrene‐ZIF‐67 yolk–shell particles as the precursor. With the structural and compositional advantages, these unique single‐holed nanocomposite hollow particles exhibit superior electrocatalytic performance for the oxygen reduction reaction.